Teaching the Islamic worldview of environmental ethics to students of science in Malaysia - Hasbullah, M.; Sadri, R.; Shah, M.H.; Azizan, S.A.; Mohd Noor, S.N. (2014)
Religion is an important cultural resource in Malaysia particularly for environmentalists who are engaged in creating new paradigms of thinking about managing the current ecological or environmental crisis. This paper presents the course content of an undergraduate course for science students entitled 'Philosophy of Islamic Science and Technology' of which a component on the 'Islamic Philosophy of Environment' is emphasized. The course is designed to particularly groom students who recognize the importance of environmental conservation and hence would act ethically towards nature. The Islamic view of nature perceives the environment in a rather different way from the modern view of nature. While the modern view of earth systems and humans may be divided into human-centric views or anthropocentrism, and natureoriented ones, or eco-centrism, Islamic environmental ethics encourages humans to see the interconnection and interdependence of all elements in the universe. It emphasizes and expounds the harmonious relationship between humankind and nature in concordance with Islamic teachings. This course also highlights an Islamic epistemology of the environment as practiced in Malaysia that has been translated in many institutions, as presented by the term "Islam Hadhari'. Islam Hadhari calls for Muslims to be progressive, modern and dynamic, and yet moderate in behavior and attitude.